Perancangan Sistem Informasi Self- Order Dengan Teknologi QR Pada Healing Cafe - Sitepu, Kezia Prissilia; Farida Gultom; Syaifuddin; Rikki Paulus Gultom (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The rapid advancement of technology in the midst of globalization has brought significant changes, especially in the field of information, especially making it easier to place orders independently. Healing cafes engaged in the culinary field are one example of a culinary business that can benefit from a self-order system. This research aims to design a QR code-based self-order system that can improve service efficiency at Healing cafes by reducing errors and improving the ordering process and making it easier for customers to order independently. This system design uses the waterfall software development method which consists of analyzing the needs of the system, system design, designing the system in the form of a program, system testing, system implementation and maintenance of the system after use. This self-order system has three main components, namely the user (customer), kitchen, and admin (cashier) whose ordering stages start when the user scans the QR code installed on the table, order data enters the kitchen system, is forwarded to the cashier system for bill printing and transaction completion. Designed without the need for a user authentication process, and supporting recurring transactions for one payment at each table are the advantages of this self-ordering system. This self-order is expected to be able to provide innovative digital solutions in managing food and beverage orders.